Is it possible to achieve an acceptable disease control by dietary therapy alone in Berardinelli Seip type 1? Experience from a case report - Cecchetti, Carolina; Belardinelli, Elisabetta; Dionese, Paola; Teglia, Rita; Fazzeri, Roberta; D’ Apice, M. Rosaria; Vestito, Amanda; Pagotto, Uberto; Gambineri, Alessandra (Frontiers in Endocrinology, 2023)
Background and Objective: Severe metabolic complications generally manifest at an early age in Berardinelli – Seip congenital lipodystrophy (BSCL) and their management is especially challenging. Nutritional intervention with low lipid personalized diets is considered by experts to be fundamental in handling the disease when associated with medical therapy, however little is known about the beneficial effects of dietary interventions alone. Aim: To underline the importance of a well-structured low-fat diet in BSCL patients. Methods and Results. A BSCL male patient strictly followed a personalized hypolipemicdiet (60% carbohydrates, 22% fats and 18% proteins) since clinical diagnosis at the age of one year. Interestingly, pharmacological interventions were not required at any point during follow up. Aged 16 years the patient was referred to our centre. Biochemistry, hormonal evaluation, 75 mg oral glucose tolerance test, cardiac evaluation and abdominal ultrasound were performed, revealing no abnormalities. Genetic analysis and leptin dosage were carried out, confirming the diagnosis of BSCL type 1 (homozygosity for c.493-1G>C pathogenic variant in AGPAT2 gene) and showing undetectable circulating levels of leptin (< 0.229 mcg/L). Diet therapy alone was therefore maintained, scheduling follow-up visits every six months, with excellent disease control ever since. Conclusions. This report proves how a personalized low-fat diet is of great help in the management of BSCL and its complications. In addition, a specific hypolipemic diet could be used alone as an effective long-term treatment in selected cases with high compliance and, probably, a milder phenotype.